Electrode-dependent asymmetric conduction mechanisms in K0.5Na0.5NbO3 micro-capacitors. (15th June 2023) - Groppi, C.; Maspero, F.; Rovelli, A.; Asa, M.; Malavena, G.; Compagnoni, C. Monzio; Albisetti, E.; Vangelista, S.; Badillo-Ávila, M.A.; Bertacco, R.
Abstract: The ultimate performance of devices employing lead-free piezoelectrics is determined not only by the intrinsic properties of the piezo, but also by processes and materials employed to create the electric contacts. In this paper, we investigate the impact of different metallic electrodes with increasing chemical reactivity (Pt, Ni, Ti, Cr), on the asymmetric behavior of the leakage current in M/K0.5 Na0.5 NbO3 /Pt(111) micro-capacitors, where M stands for the top metallic electrode. For all electrodes we found a marked leakage asymmetry that we ascribed to the presence of a Schottky-like rectifying junction at the M/K0·5 Na0·5 NbO3 /Pt(111) bottom interface, while the corresponding junction at the top interface is deeply affected by the creation of oxygen vacancies due to oxygen scavenging during the growth of the top metallic electrodes, leading to an almost ohmic top contact. The leakage increases with the reactivity of the electrodes, while the asymmetry decreases, thus suggesting that the creation of the top metal/K0·5 Na0·5 NbO3 interface generates oxygen vacancies diffusing down to the bottom interface and impacting on the rectifying behavior of the Schottky-like junction. Noteworthy, this asymmetric conduction can reflect in an asymmetric piezoelectric and ferroelectric behavior, as a sizable portion of the applied voltage drops across the rectifying junction in reverse bias, thus hampering symmetric bipolar operation, especially in leaky materials.